A two-stage algorithm for computation of the exact distribution of sums of spacings. Issue 10 (26th November 2017) - Lin, Chien-Tai; Lu, Chung-Tao
ABSTRACT: Based on the recursions in Huffer (1988 ) and Huffer and Lin (2001 ), we present a two-stage algorithm and two specialized methods for evaluating the probabilities involving linear combination of spacings of special forms. The two-stage algorithm combines the advantages of marking algorithm in Huffer and Lin (1997 ) and general algorithm in Huffer and Lin (2001 ). The proposed methods can analytically derive the exact expressions for some specific problems, and efficiently handle problems such as the distribution of the circular scan statistic and multiple coverage probabilities.